2021
DOI: 10.3390/nu13010197
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Medicinal Properties of Tualang, Gelam and Kelulut Honeys: A Comprehensive Review

Abstract: Tualang, Gelam and Kelulut honeys are tropical rainforest honeys reported to have various medicinal properties. Studies related to the medicinal properties and physicochemical characteristics of these honeys are growing extensively and receiving increased attention. This review incorporated and analysed the findings on the biological and physicochemical properties of these honeys. Tualang, Gelam and Kelulut honeys were found to possess a wide variety of biological effects attributed to their physicochemical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 150 publications
(136 reference statements)
1
31
1
Order By: Relevance
“…Honey is known to affect dipsogenic hormones and cause an anti-dipsogenic effect. Angiotensin II and serotonin are dipsogenic hormones that are able to increase thirst perception, resulting in an increased water intake [9,29]. However, in the present study, the rats receiving higher doses of GH experienced anti-dipsogenic effects and ultimately reduced their water intake.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Honey is known to affect dipsogenic hormones and cause an anti-dipsogenic effect. Angiotensin II and serotonin are dipsogenic hormones that are able to increase thirst perception, resulting in an increased water intake [9,29]. However, in the present study, the rats receiving higher doses of GH experienced anti-dipsogenic effects and ultimately reduced their water intake.…”
Section: Discussioncontrasting
confidence: 60%
“…The most prevalent monosaccharides are fructose and glucose. Honey is known as a promoter of general health with antibacterial, antioxidative, anti-inflammatory, anti-cancer, anti-adiposity and woundhealing properties [9]. The substance exerts beneficial effects on neurology with known anxiolytic, anti-nociceptive, anti-convulsant and anti-depressant effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, honey colour is dependent on potential alkalinity and ash content, as well as the presence of antioxidative active pigments, including carotenoids and flavonoids [ 32 ]. In addition, differences in honey composition can influence the value of specific honey types for medicinal or health-promoting purposes [ 2 , 33 ]. Nevertheless, the main constituents of all honey types from all countries around the world are almost similar.…”
Section: Production and Variations In Honeymentioning
confidence: 99%
“…It mainly comprises 38% fructose, 31% glucose and a small amount of a complex mixture of disaccharides, trisaccharides, maltose, maltulose and oligosaccharides. It contains a wide variety of essential bioactive compounds, as well as various types of enzymes, including amino and organic acids, acid phosphorylase, phytochemicals, carotenoid-like substances, vitamins and minerals [ 1 , 2 ]. It also contains a trace amount of vitamin A (retinol), vitamin E (tocopherol), vitamin K (an antihaemorrhagic vitamin), vitamin B1 (thiamine 1), vitamin B6, vitamin C (ascorbic acid), niacin, folic acid, minerals and iron zinc [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, honey has antioxidant, antibacterial, anti-cancer, anti-inflammatory, antidepressant, anxiolytic, and anti-stress properties [ 16 ]. Previous reviews on Tualang honey showed comparative differences in medicinal properties [ 13 ], potential anti-cancer properties [ 17 ], and physicochemical properties [ 18 ]. Although the potential roles of honey and honeybee products in neurological actions [ 19 ] as well as in learning and memory have been reviewed [ 20 ], other potential neurological effects, particularly of Tualang honey, remain to be comprehensively reviewed.…”
Section: Introductionmentioning
confidence: 99%